IMPACT OF COVID-19 ON EDUCATION IN INDIA: CHALLENGES AND DETERMINANTS OF TEACHER ENGAGEMENT IN REMOTE TEACHING (International Journal of Food and Nutritional Sciences, 2022)
This paper focusses on the COVID-19 pandemic's effects on Indian school systems, particularly focusing on the challenges faced by teachers in transitioning to remote teaching. It also aims to explore the determinants of employee engagement among teachers teaching remotely, with a specific emphasis on the quality of student involvement. The study highlights the stress and effort teachers are experiencing due to the shift to online platforms like Zoom, Teams, and Google Meet, and how environmental factors such as work stress and workload can affect teacher engagement. It also emphasizes the importance of instructor-student communication and active student engagement in predicting teacher work engagement. The research suggests that further investigation is needed to understand engagement in online education and its influencing factors to improve teacher commitment and ensure the long-term viability of the Indian education system